Taking Science Home: Connecting Schools and Families Through Science Activity Packs for Young Children. (January 2016) - Reinhart, Meredith; Bloomquist, Debra; Strickler‐Eppard, Lacey; Czerniak, Charlene M.; Gilbert, Amanda; Kaderavek, Joan; Molitor, Scott C.
Abstract : A Framework for K‐12 Science Education indicates that introducing young children to scientific and engineering practices, core disciplinary ideas, and crosscutting concepts during the early years is essential for the development of conceptual understanding in science. Unfortunately, science is infrequently included in preschool and primary classrooms, and parents are sometimes uncomfortable engaging their children in science. This article describes the development and initial evaluation of "family science activity packs" as an intervention to fill this void. The study examined four research questions focused on families' use of the packs, parental questions, children's inquiry behaviors, and the nature of parent and children's reactions to the packs. Questionnaires sent to families regarding the packs and videos of families completing the activities were analyzed using descriptive statistics and qualitative methods. Findings suggest that take‐home activity packs have the potential to teach science in a motivating manner and spur further interest in science. However, parent questioning and wait‐time impacted the quality of students' responses. A discussion of how family science activities potentially result in high‐quality discourse is presented, and implications and suggestions for further research and pack development are reviewed. This article features aResearch to Practice Companion Article . Please click on the supporting information link below to access.